Biological effects of formulation containing curcuminoids and Bidens Pilosa L. in oral carcinoma cell line - Diego Antonio Costa Arantes; Artur Christian Garcia da Silva; Eliana Martins Lima; Ellen Cristine Pineze Alonso; Ricardo Neves Marreto; Elismauro Francisco Mendonça; Marize Campos Valadares; Aline Carvalho Batista (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract: FITOPROT, which contains curcuminoids and Bidens pilosa L. extract, is an innovative mucoadhesive formulation indicated for the topical treatment of chemoradiotherapy-induced oral mucositis (OM) in patients with advanced and visible oral squamous cell carcinoma. The formulation is used as a mouthwash directly on tumor tissue of patients with advanced neoplasms, without triggering cancer cell proliferation or tumor invasiveness. Thus, the aim of this study was to evaluate the biological effects of FITOPROT on an oral squamous cell carcinoma cell line (SCC-4). The viability of SCC-4 cells was assessed after exposure to FITOPROT using MTT reduction assay. The effects of the mucoadhesive formulation on cell cycle progression and cell death parameters were evaluated using flow cytometry. In addition, the inflammatory profile of the tumor cells was evaluated using the cytometric bead array (CBA) assay. FITOPROT promoted a concentration-dependent decrease in cell viability and cell cycle arrest at the G2/M phase (p < 0.05). Mitochondrial membrane potential was also altered after exposure to the formulation (p < 0.05), in parallel with a reduction in VEGF and IL-8 production (p = 0.01 and p = 0.05, respectively). In summary, the results indicate that FITOPROT reduces SCC-4 cell viability, promotes cell cycle arrest, modulates mitochondrial membrane potential, and exhibits antiangiogenic and anti-inflammatory properties, thus indicating its potential for topical use in patients with OM and visible tumors in the mouth.